Pemanfaatan Mikroalga dalam Penurunan Kadar Amonia dengan Variasi Penambahan Effective Microorganism - Anshah Silmi Afifah; Gita Prajati; Yosef Adicita; Darwin Darwin; Yura Witsqa Firmansyah (Jurnal Serambi Engineering, 2021)
The existence of microalgae in water -provides many benefits especially for biological treatments of wastewater. Microalgae have many species and are chlorophyll microorganisms. Photosynthesis carried out by microalgae requires essential nutrients such as CO2. Carbon dioxide can be obtained by symbiosis from other microorganisms, such as EM4, which can be used to decompose complex organic compounds into simple compounds (CO2). The addition of EM4 must be appropriate to make the photosynthesis process in microalgae take place optimally. Therefore, this study aims to determine the optimal dose variation of EM4 in the microalgae in the reactor. With variations in the doses tested were 0 mL, 1 mL, and 2 mL. The research was conducted by making artificial wastewater from liquid NPK, diluting it with tap water with a ratio of 1: 300. The test was carried out using a batch system, with solar lighting and aeration for 24 hours. The result of the best dose variation is the addition of 1 mL of EM4.  The largest decrease in ammonia levels is obtained which is then compared to the variation of the doses of 0 mL and 2 mL.